A Preliminary Study of Anatomical Changes Following the Use of a Pedicled Buccal Fat Pad Flap During Primary Palatoplasty. (May 2022) - Kotlarek, Katelyn J.; Jaskolka, Michael S.; Fang, Xiangming; Ellis, Charles; Blemker, Silvia S.; Horswell, Bruce; Kloostra, Paul; Perry, Jamie L.
Objective: The purpose of this study was to examine the surgical impact of the pedicled buccal fat pad (BFP) flap on the levator veli palatini (LVP) muscle and surrounding velopharyngeal (VP) anatomy following primary palatoplasty using magnetic resonance imaging (MRI). Design: Observational, prospective. Setting: MRI studies were completed at 3 different facilities. All participants with BFP flap were operated on by the same surgeon. Participants: Five pediatric participants with cleft palate with or without cleft lip (CP±L) who underwent primary palatoplasty with BFP flap placement. Comparison groups consisted of 10 participants: 5 with CP±L who did not receive the BFP flap and 5 healthy controls. Interventions: All participants underwent nonsedated MRI 2 to 5 years postoperatively. Main Outcomes and Measures: Anatomical measures of the velopharynx and LVP among the 3 participant groups. Results: Median values were significantly different among groups for velar length ( P = .042), effective velar length ( P = .048), effective VP ratio ( P = .046), LVP length ( P = .021), extravelar LVP length ( P = .009), and LVP origin–origin distance ( P = .030). Post hoc analysis revealed a statistically significant difference between the BFP and traditional repair groups for effective VP ratio ( P = .040), extravelar LVP length ( P = .033), and LVP length ( P = .022). Conclusions: This study provides preliminary support that the BFP flap creates a longer velum, with increased distance between the posterior hard palate and the LVP, and a larger effective VP ratio compared to traditional surgical techniques. Future research is needed to determine whether this procedure provides a more favorable mechanism for VP closure.